African American Faculty in Social Work Schools: A Citation Analysis of Scholarship. (March 2018) - Huggins-Hoyt, Kimberly Y.
Purpose: This study assessed the research productivity of African American faculty in the top 25 ranked schools of social work cited in the 2012 U.S. News and World Report. Method: Four citation metrics ( h -index, g -index, age-weighted citation rate, and per author age-weighted citation rate) were examined. Results: Scholar rankings per h -index changed when ranked by other metrics revealing more uniqueness beyond the impact of their scholarship. Discussion: While the h -index metric is a valuable measure of scholarly impact to assist tenure and promotion decisions, it should be considered with other metrics that reveal the overall character of individual scholarship. As the overall research culture of social work broadens, future research calls for an expanded knowledge based on measuring both impact and uniqueness of scholarship to assist faculty, especially minority scholars, in successfully negotiating and overcoming barriers and challenges.